World atlas of Holocene sea-level changes - Pirazzoli, P. A. (Paolo A.) (Elsevier oceanography series, 1991)
This timely study is concerned with the current record of sea-level changes during the past 10,000 years; their rates, and our ability to estimate these changes accurately. The author begins with an extensive introduction to the subject, covering the historical background and the possible causes of sea-level changes and the main methods used to reconstruct former sea-level positions. The second and main part of the Atlas provides a worldwide review of Holocene sea level changes by assembling some 800 local relative sea-level curves, deduced from field data from all parts of the world, and comparing these with over 100 curves predicted by geophysical models. This data is compiled in 77 regional plates, each containing 4-20 relative sea-level curves drawn to the same scale. These plates enable a visual assessment of geological trends in sea-level during the Holocene to be made. Comparing this data with trends deduced from tide gauges and near-future trends predicted by climate models, should enable more accurate assessment of near future sea-level changes on a local scale. The regional plates are fully annotated with locations, authors' names, year of publication and some indicative values of the spring tidal range in the region, as well as an accompanying text of comments. Finally, the author provides a state of the art review, proposes improvements in methodology and suggests directions for further study. An extensive bibliography of over 750 references, and two indexes complete the study. This comprehensive work contains data and interpretations of value to all those with an interest in regional geography, climatology, sea-level change, and environmental science.